Класифікація дифузії результатів інноваційної діяльності підприємств - Ванькович, Л. Я. (Видавництво Львівської політехніки, 2016)
Розглянуто існуючі види дифузії результатів інноваційної діяльності підприємств, зокрема за типом дифузора та видом моделі дифузії. Класифікація дифузії результатів інноваційної діяльності підприємств розширена на види за такими класифікаційними ознаками, як об’єкт, рівень і географічне охоплення. Кожний з видів названий, описаний і обґрунтований з позицій можливості чи необхідності його виділення. Побудована шкала оцінювання рівня дифузії результатів інноваційної діяльності підприємства. Виділено групи дифузерів та їхні характеристики з позицій інноваційної активності дифузерів і їхньої схильності до ризику. Were considered existent types of diffusion of results of innovative activity, including the kind of diffuser and the type of diffusion model. Classification of diffusion of results of innovative activity expanded views on classification features as an object, level and geographic coverage. Each of the kinds named, described and justified from the standpoint of possibility or necessity of his selection. Constructed scale estimation of a level diffusion of results of innovative activity of enterprise. Highlight of the diffuser and its characteristics from the standpoint of innovation activity and their appetite for risk. To ensure the rational management of diffusion of results of innovative activity of enterprises, it is necessary to identify and systematize kinds of diffusion. This need caused by the necessity get the most complete and specific information about objects diffusion, especially the stages of development of the phenomenon of diffusion. From the level of awareness diffusers depends rationality endorse their decisions, including the choice of strategy and tactics diffusion of results of innovative activity of enterprise and of operative interference in distribution of diffusion’s objects on the market. As for the classification of diffusion of innovations, it is investigated in a small number of studies. So the problem is not sufficiently disclosed and requires further study. The study aims is to develop a classification of diffusion of results of innovative activity enterprises. By the object is expedient to allocate the following kinds of diffusion of results of innovative activity enterprise: the diffusion of creative ideas are brought to the level of knowhow; diffusion of innovations (innovative products, innovative technologies); diffusion of ownership of using innovation and brands. These kinds diffusion is expedient single out because each of these of objects is different dissemination in the market, accompanied specificity factors that influence the phenomenon of diffusion various risks and possibilities of applying results of innovative activity to get the desired effect. By the level of diffusion offer allocate a very low, low, medium, high and very high diffusion results of innovative activity enterprise. This graduation is important because of the need for evaluation of dissemination results of innovative activity in a particular sector (national market, region, etc.). Based on the number of potential customers (users) certain result of innovation activity of specific environment it is possible to estimate the level of diffusion. Diffusion by a geographical coverage is expedient to allocate for comparability levels of diffusion in time and space, the selection of its pace. Consequently, by a geographical scope distinguish national diffusion (diffusion in micro, meso and macro levels) and international diffusion (regional, continental, intercontinental, global). As a result of the research classification diffusion of results of innovative activity of companies was expanded by the author in the following of kinds classifications, an object, a level and a geographic coverage. Each of the kinds named, described and justified from the standpoint of possibility or necessity of his selection. However, there is some probability in the selection of other kinds or signs in further research theoretical and practical aspects of diffusion of innovation. It is worthwhile also investigate models of diffusion of results of innovative activity.
The classification of diffusion of results of innovative activity
Keywords: дифузія інновацій; дифузії результатів інноваційної діяльності підприємств; класифікація дифузії інновацій; види дифузії результатів інноваційної діяльності підприємства; групи дифузерів; моделі дифузії; diffusion of innovation; diffusion of results of innovative activity; classification of diffusion of results of innovative activity; kinds of diffusion of results of innovative activity; types of diffusers; models of diffusion